Phonological Deviations Produced By Dyslexic Adolescent in Indonesian Language - Kirana, Angkita Wasito; Syukri, Masitha Achmad; Endriastuti, Annysa (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2025)
Despite Indonesian’s transparent orthography and frequent reading exposure, dyslexic students continue to experience reading impairments into adolescence. This study aimed to analyse the phonological deviations observed during dyslexic adolescents’ reading activities in an inclusive school in Surabaya. This qualitative study involved face-to-face reading tests using a corpus-informed instrument comprising 180 phonologically selected keywords arranged into 55 sentences, administered to two adolescent participants with dyslexia. Of 55 total errors, 33 were phonological; most outputs were non-words (20/33). Feature-changing was the predominant process (16/33), typically preserving at least one feature (often place of articulation), consistent with subtle but systematic sub-lexical grapheme–phoneme mapping weaknesses. Vulnerabilities clustered around velar segments (/k, g, ŋ, x/) and high-load contexts—consonant clusters (e.g., /st/, /tr/), digraphs (<ng>, <kh>), and vowel/consonant sequences—often managed via epenthesis (e.g., schwa insertion in /st/, /ŋ/→/ŋg/) or deletion (e.g., coda /k/). Some patterns (e.g., /v/→/f/, /ʃ/→/s/, schwa in /st/) aligned with Javanese phonotactics, while others (e.g., certain velar substitutions) were not L1-explainable, underscoring a core phonological-decoding deficit. Findings indicate that, even after years of literacy exposure, phonological decoding remains the major handicap for Indonesian-speaking dyslexic adolescents; assessments and interventions should therefore target sub-lexical mapping in clusters, digraphs, codas, and velars, while accounting for local phonotactic influences.